Digitalization in Higher Education: How Information Systems Improve Operational and Strategic Performance - Yunianto Agung Nugroho; Adi Widodo; Erni Taruli Pebrina; Joni Iskandar; Multi Nadeak (International Journal of Management and Economic Research (IJOMER), 2025)
This study explores the strategic and operational impacts of digitalization in higher education institutions (HEIs), focusing on the role of information systems (IS) as enablers of institutional performance. Anchored in a qualitative multi-case study design, the research investigates how IS enhance administrative efficiency, support data-driven decision-making, and navigate the sociotechnical challenges of digital transformation. Guided by the Technology-Organization-Environment (TOE) framework and the Resource-Based View (RBV) theory, the study draws on in-depth interviews, participant observation, and institutional document analysis across universities with differing levels of digital maturity. Findings reveal that IS significantly improve service delivery and strategic agility, particularly through analytics integration and automation of academic workflows. However, barriers such as organizational resistance, digital literacy gaps, and infrastructure limitations constrain transformation outcomes. The study contributes to theory by integrating TOE and RBV in analyzing IS adoption, and to practice by offering actionable insights for institutional leaders. It concludes that digital transformation is not purely technological but deeply human and contextual—requiring adaptive leadership, inclusive strategies, and sustained investment in digital capacity.